The retable of the chapel of Our Lady of Mercy in the cloister of Oporto’s Cathedral: study, conservation and restoration - Monteiro, Patrícia (2018)
The retable located in the Chapel of Our Lady of Mercy, in the cloisters of Oporto’s cathedral, dates back to the 17th century. Artistically, it belongs to a transition period between the Mannerism and the Baroque styles. The artistic value and the lack of documented information about the artwork led to the development of a project contemplating its the study. Both chemical and physical analyses - observation of the support, micro-FTIR and SEM-EDS - suggest that the retable was carved in sweet chestnut wood, accordingly to the techniques used at the time. The retable presents water-gilded areas contrasting with blue and red phytomorphic motifs. The polychromed areas were later covered with lead white paint. There were also evidences of previous conservation-restoration interventions. The frail condition of the retable’s materials testified the need to conserve and restore it. Among other procedures, the materials were consolidated and the lacunae were filled and inpainted - partially regenerating the artwork’s aesthetic unity.